Interaction of methyl-3-[(dimethylamino)methylidene]-4-oxo-6-fluoro-3,4-dihydro-2H-chromane-2-carboxylate with aromatic amines - Kysil, A. I.; Moskvina, V. S.; Turov , A. V.; Voitenko, Z. V.; Khilya, V. P. (Reports of the National Academy of Sciences of Ukraine, 2015)
A convenient efficient method for the synthesis of methyl-3-[(dimethylamino)methylidene]-4-oxo-6-fluoro-3,4-dihydro-2H-chromane-2-carboxylate has been proposed. The interaction of methyl-3-[(dimethylamino)methylidene]-4-oxo-6-fluoro-3,4-dihydro-2H-chromane-2-carboxylate with aromatic amines has been studied. It has been demonstrated that the obtained 3-(aminomethylen)-6-fluorochroman-4-oxo-2-carboxylates exist in a solution as a mixture of Z/E-isomers with respect to the exocyclic double C=C bond. With the help of NMR methods, it is proved that the determining factor in the isomeric composition is solvation effects, and the balance can easily shifted t toward one of the isomers.